Assessing Morocco’s Transition to a Green Economy: An Indicator-Based Analysis (2010–2020) - Bouayad, Meryam; Hamdaoui, Mohamed (European Scientific Journal, ESJ, 2026)
While Morocco has embarked on an ambitious transition to a green economy, assessing its actual progress remains a challenge. Drawing on previous work on green economy indicators and progress assessment frameworks, this study aims to assess and project the dynamics of the green economy in Morocco over the period 2010–2020. The methodology selects and operationalizes 13 quantitative indicators aligned with national strategic priorities (including the share of renewable energy, GHG emissions, and protected areas) sourced from official national and international databases. These indicators are normalized using a min-max approach and aggregated with equal weighting into an annual composite Green Economy Index (GEI). The results reveal a clear improvement in the GEI, rising from 0.263 ("Low") in 2010 to 0.754 ("Above Average") in 2020, demonstrating the positive impact of investments in renewable energy and water management. However, this trajectory is uneven and vulnerable to exogenous shocks, as evidenced by the contraction in 2015 linked to a severe drought, and masks persistent structural challenges in the transport and industrial sectors. The study concludes that Morocco has laid solid foundations but that achieving a "High" performance level will require more profound structural reforms. Limitations include data availability constraints and the equal weighting of indicators. The main contribution lies in providing a reproducible monitoring tool and a basis for future comparative analyses.